2016
DOI: 10.1186/s12887-016-0639-1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the international normalized ratio of neonates and its relationship with ambient temperature

Abstract: BackgroundThe morbidity and mortality rates due to cardiovascular events such as myocardial infarction are known to exhibit seasonal variations. Moreover, changes in the ambient temperature are reportedly associated with an increase in these events, which may potentially involve blood coagulation markers. Bleeding due to vitamin K deficiency in neonates, which is associated with high mortality and a high frequency of neurological sequelae, is more commonly observed during the summer season and in warm regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…Therefore, dehydration of the newborn during the warm season is unlikely. Regarding the room temperature, our previously published paper reported that the room temperature in the neonatal ward was unchanged throughout the year [24]. Moreover, in the present study, the rate of breastfeeding of neonates was not different between those born in the warm and cold seasons.…”
Section: Discussionsupporting
confidence: 48%
“…Therefore, dehydration of the newborn during the warm season is unlikely. Regarding the room temperature, our previously published paper reported that the room temperature in the neonatal ward was unchanged throughout the year [24]. Moreover, in the present study, the rate of breastfeeding of neonates was not different between those born in the warm and cold seasons.…”
Section: Discussionsupporting
confidence: 48%
“…Therefore, dehydration of the newborn during the warm season is unlikely. Our previously published paper reported that room temperature in the neonatal ward was unchanged throughout the year [19]. Moreover, in the present study, the rate of breastfed neonates was not different between those born in the warm and cold seasons.…”
Section: Discussionsupporting
confidence: 57%
“…As the body's central temperature is tightly regulated and under normal circumstances not directly associated with ambient temperatures, it remains an open question how outside temperature could modulate the incidence of GIB. It has, however, been reported that bleeding time as well as clotting time are dependent on ambient temperature in vitro [15] as well as in vivo [16] and might even show seasonal variations [17]. Hypothetically, a prolonged bleeding time as well as an impaired clotting time associated with lower temperatures may increase the risk for overt bleeding events.…”
Section: Discussionmentioning
confidence: 99%